Mariana Porras (2011)
Mariana was 10 when she first came to EAFIT Children's University, is now 17, pursues two undergraduates degrees and is a mentor in Expeditions to Knowledge. For her, academic life is an option; she does not pretend to be the best, but she says she really likes to know and explain to others.